Strategi Pengawasan Komisi Penyiaran Indonesia (KPI) Aceh Terhadap Tata Kelola Isi Siaran di Aceh - Serliana, Serliana; Muzakkir, Muzakkir (CV. Publikasi Indonesia, 2022)
The Indonesian Broadcasting Commission (KPI) is an independent or stand-alone institution, this institution consists of two, namely the Central Regional Broadcasting Commission and the Regional Regional Broadcasting Commission. This study describes how the performance of the Indonesian Broadcasting Commission, especially in the Aceh region, on the management of broadcast content in Aceh, it is very useful so that later broadcasts that are widely circulated and widely enjoyed by the public can be useful and do not violate the Indonesian broadcasting law. The purpose of this study is to find out how the governance of broadcast content in Aceh is carried out by the Indonesian Broadcasting Commission (KPI), especially in the Aceh region and minimize errors so that broadcasters will comply with regulations. The method used in this research is using qualitative research methods with a qualitative descriptive approach, with data collection techniques carried out by means of observation, interviews and documentation. Data analysis was carried out by means of data reduction, data presentation, conclusion drawing and verification. The results of this study indicate that the Aceh Regional Indonesian Broadcasting Commission only acts as a regulator of content distribution in Aceh. However, the current manpower shortage and availability of experts for good governance is far from over. In addition, the lack of budget for the procurement of competent monitoring equipment is one of the main obstacles faced by the Aceh KPID. So it can be concluded that the Indonesian Broadcasting Commission in Aceh has carried out the management of broadcast content to the maximum extent possible, and is supported by several parties who have helped in monitoring the broadcast content that is disseminated.